Digital transformation of attendance systems using applications at H&CO enterprises - Ade Fitri Arnita Sinaga; Cece, Cece (SEAN Institute, 2024)
The purpose of this research is to know how the digital transformation of the attendance system uses applications in the H&Co business. The data analysis used in this research is a qualitative descriptive method by conducting an interview with one of the employees who works at the H&CO company and direct observation at the research site which is then used as primary data. The documentation study was carried out by collecting data from the company. Library research is looking for reference sources such as journals and theses as previous research, as a reference or basis for analyzing the attendance system used by the company. From the results of research regarding the digital transformation of the attendance system using applications in the H&Co business, namely the existence of an application-based attendance information system, making it easier for employees to take absences easily, quickly and on time according to their work schedule, can increase work morale and loyalty to the company. , can increase the effectiveness and efficiency of data processing quickly and accurately, can avoid or minimize actions that are bad or detrimental to the company.